Homophily and social norms in experimental network formation games - Jasmina Arifovic; Giuseppe Danese (Games, 2018)
Field studies of networks have uncovered a preference to befriend people we perceive as similar according to some dimensions of our identity ('homophily'). Lab studies of network formation games have found that adherence to social norms of reciprocity and inequity aversion are also drivers of network choices. No study so far has attempted to investigate the role of both homophily and social norms in a controlled environment. At the beginning of our experiment, each player fills in a personal profile. Each player then views the profile of all other players and expresses a degree of perceived similarity between his/her profile and the profile of the other player. At this point, a repeated network formation game ensues. We find that: (1) potential homophily considerations triggered by the profile rating task did not measurably change the players' behavior compared to the baseline; (2) reciprocity plays a significant role in the formulation of the players' strategies, in particular lowering the probability that the player naively best responds to the network observed in the previous period. We speculate that reciprocation of past choices might be a more 'available' aid in strategy-formulation than considerations related to the similarity of the other players.
Keywords: C91; D85; D01; 330; networks; identity; heterogeneity; homophily; reciprocity; inequity